2022
DOI: 10.1007/s00167-022-06929-0
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular joint suture button repair leads to coracoclavicular tunnel widening

Abstract: Purpose Biomechanical evaluation of three different suture button devices used in acromioclavicular joint repair and analysis of their effect on post-testing tunnel widening. Methods Eighteen human shoulder girdles were assigned into three groups with a similar mean bone mineral density. Three different single-tunnel acromioclavicular repair devices were tested: (1) AC TightRope® with FiberWire; (2) AC Dog Bone™ Button with FiberTape; (3) Low Profile AC Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…More recently, the phenomenon of tunnel widening of the clavicular tunnels has gained attention and could attribute to an increased risk of loss of reduction and clavicle fractures 2 . Recent clinical studies however do not support a relationship between tunnel widening and loss of reduction or clinical outcome [12][13][14] . Studies investigating this phenomenon detected a tunnel widening in up to 100% of the patients, with a mean increase in tunnel diameter of 18-66% [12][13][14][15] .…”
Section: Discussionmentioning
confidence: 95%
“…More recently, the phenomenon of tunnel widening of the clavicular tunnels has gained attention and could attribute to an increased risk of loss of reduction and clavicle fractures 2 . Recent clinical studies however do not support a relationship between tunnel widening and loss of reduction or clinical outcome [12][13][14] . Studies investigating this phenomenon detected a tunnel widening in up to 100% of the patients, with a mean increase in tunnel diameter of 18-66% [12][13][14][15] .…”
Section: Discussionmentioning
confidence: 95%
“…The current study showed posterior translation of the distal clavicle relative to the scapula with shoulder motion, implying that the reconstructed CC ligament might be overstressed on the anterior part of the clavicular tunnel with shoulder movements, resulting in cumulative damage over time. 4,6 Meanwhile, it was reported that the distal clavicle translates posteriorly because of traction of the upper trapezial muscle when AC dislocations occur. 9 Consequently, an anterior-inferior tunnel from the superior-posterior clavicular surface instead of a vertical one is more likely to provide native stability and should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this is the first in vivo study to draw attention to the possible cause of failure and attempt to correlate it to coracoid tunnel widening. An in vitro study by Dalos et al used micro-CT analysis to assess coracoid and clavicular tunnel widening and compared them across three different repair systems [ 10 ]. They reported tunnel widening at 5 different tunnel cross sections and found that tunnel widening mainly occurs at the inferior part of the clavicular tunnel followed by the superior part of the coracoid tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of arthroscopic-assisted fixation of acute ACJ injury is to use suspensory devices to maintain the coracoclavicular distance and facilitate healing of the CC and AC ligaments [ 21 , 26 ]. These suspensory devices require the drilling of tunnels into the clavicle and the coracoid, which yields complications, such as fracture of the distal clavicle and coracoid and tunnel widening with biomechanical consequences [ 10 , 22 ]. Also, loss of reduction is a commonly found complication with an incidence ranging from 12 to 80% after arthroscopic techniques [ 9 , 11 , 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%